Directional Torsion Sensor Based on a Paired Helical-Type Multimode Fiber - Wenlei Yang; Ke Tian; Le Li (Sensors)
A torsion sensor with directional discrimination based on a single-mode–twisted multimode–single-mode (STMS) fiber structure is demonstrated. The STMS fiber structure is fabricated by fusion-splicing a segment of multimode fiber (MMF) between two single-mode fibers (SMFs), where the MMF is simultaneously heated and twisted to form paired helical-type structures. The experimental results indicate that the resonance wavelength shifts towards shorter wavelengths as the twist rate increases in the clockwise direction, while an opposite shift occurs in the counterclockwise direction. Within a twist rate range of −5.2 rad/m~5.2 rad/m, the wavelength and transmission sensitivities are determined to be −1.38 nm/rad·m−1 and 3.12 dB/rad·m−1, respectively. Furthermore, the proposed twist sensor exhibits minimal temperature crosstalk of 0.0072 (rad/m)/°C, making it highly desirable for mitigating temperature-induced cross-sensitivity in torsion measurement applications.